The Cyclicality of Fiscal Policy in the Middle East and Central Asia : Is the Current Crisis Different? (IMF Working Papers; Working Paper ;, 2010)
The countries of the Middle East and North Africa, and the Caucasus and Central Asia have the highest output volatility in the world. Fiscal policy is a powerful tool that can help dampen the business cycles. This paper analyzes the cyclical properties of fiscal policy in the region during the past four decades and explores whether the response during the current global economic crisis is different in 2009. Across a sample of 28 countries, we find that fiscal policy has typically amplified the business cycles and that it has been more procyclical in good times than in bad times. However, the response to the current crisis has differed from the past in that about half of the countries responded countercyclically in 2009. Going forward, the fiscal space during downturns varies widely across countries, depending on the level of debt, access to capital markets, and natural resource wealth. Not surprisingly, the oil exporters have more fiscal room than oil importers, although there are some oil importers that still have room to respond countercyclically in bad times.